Morphology and phase inversion of EPDM/PP blends – effect of viscosity and elasticity - Antunes, Carla Filipa Melo Silva (2011)
This work aims to study the effect of viscosity and elasticity ratios on the morphology and phase inversion of ethylene propylene diene monomer (EPDM)/polypropylene (PP) blends. EPDM/PP blends with a wide range of viscosity ratios and compositions were prepared in a Haake batch mixer under constant processing conditions. The composition range of EPDM/PP co-continuous morphology was investigated by selective solvent extraction and scanning electron microscopy (SEM). For the viscosity ratios used (10 3 to 102), a substantial composition range of co-continuity morphology was found. Our results suggest that the melt viscosity and elasticity of the major phase are the main parameters that govern the co-continuity region and phase inversion. Results obtained for phase inversion compositions were also compared with those predicted by several empirical models developed to predict the phase inversion point using dynamic viscoelastic properties of blend components. A good fit of our experimental results was obtained by adjusting the general relationship of the composition as a function of the viscosity ratio and by introducing an exponent and prefactor.